Impacts of organisational role and environmental factors on moral injury and trauma amongst police investigators in Internet Child Abuse Teams. (March 2023) - Doyle, Mark; Tapson, Kit; Karagiannopoulos, Vasileios; Lee, Peter
Little is known about how the effects of moral injury and trauma manifest amongst police Internet Child Abuse Teams. This article reports on the impacts of organisational role and environmental factors on moral injury and trauma amongst this population. Six participants were recruited from two police constabularies in the United Kingdom. Data were analysed using interpretative phenomenological analysis. Findings indicated that the participants' moral injury and trauma were predominantly attributable to excessive workloads and stigma in relation to mental health within policing. Generic psychological interventions were insufficiently responsive to the complex needs of the police investigators.